Comparison of Sexual Self-Efficacy, Self-Differentiation and Communication Patterns in Iranian Women with Early and Typical Marriage: Sexual self-Efficacy, Self-Differentiation & Communication Patterns in Iranian women with Early marriage & Normal marriage. - Pourmohseni-Koluri, Fereshte; Adli, Maryam; Jafari, Eisa; Hadian, Sahel; Gasemi, Masoome (International Journal of Applied Behavioral Sciences, 2023)
Background and Aim:Marriage is one of important social phenomena that has a very sensitive role on all aspects of human life and having physical, psychological and social preparation is necessary for it. The age which individual gets married is one of the important factors that can affect the quality of marriage and its psychological function. This study aimed to compare sexual self-efficacy, self-differentiation and communication patterns in early marriage and normal marriage. Materials and Methods:The method of the present study was causal-comparative. The statistical population included all women referred to Ardabil Health Center who were married under the age of 18 and over the age of 18 or older and both groups of women lived in Ardabil in 2019. The sample of the present study consisted of 40 individuals who were selected by convenience sampling method. Also, 40 women with normal marriage conditions who were matched with their spouse’s child group in terms of age, level of education were selected by available meansCouples Communication Patterns Questionnaire,Self-Differentiation Questionnaire and completed Sexual Self-Efficacy. Data were analyzed using multivariate analysis of variance. Results:The results showed that sexual self-efficacy, self-differentiation, constructive communication pattern and avoidance-reciprocal communication pattern were significantly different between the two groups (p<0.05) and observed a difference in the expectation/withdrawal communication subscaleno difference was observed. Conclusion:In explaining communication problems and use of incompatible communication methods in early marriage, it can be said that EM, increases likely hood of communication violence Another explanation observed in early marriage is the lack of right to choose the right one to marry and preparation for having sex which reduces couple`s marital intimacy, intensifies marital conflicts, and increases the possibility of violence in couples’ relationships and ineffective communication patterns. Another finding in this survey indicated that self-differentiation in EM is less than later marriage women. In explaining this finding, it can be said that child marriage often happens during adolescence. It is the stage of transition to adulthood, gaining new experiences and facing new challenges.